Peningkatan Hasil Belajar Ekonomi melalui Metode Ekspositori pada Siswa Kelas XI IPS 3 SMAN 1 Koto Balingka - Desmawati Desmawati (Journal of Education on Social Science (JESS), 2017)
The purpose of this study was to improve student learning outcomes in economic subjects through expository learning methods in students of class XI IPS 3 SMA Negeri 1 Koto Balingka in the school year of 2015/2016. This study was conducted through classroom action research. Data in this study were collected through several techniques that are (1) observation, (2) documentation, (3) cycle final test. Data were analyzed by using analysis of class score average, classical learning completeness, student activity observation, and questionnaire on student responses. The results of this study indicated that there is an increase in student learning outcomes before and after the action at the end of the first cycle with the average scores and percentage of learning mastery that increased from cycle I to cycle II, that is from the average score of 71.9 to 83.3 with the score of minimum mastery criteria (KKM) of 76. Thus it could be concluded that economic learning through expository learning method could improve student learning outcomes in class XI IPS 3 SMA Negeri 1 Koto Balingka.